ILLOCUTIONARY ACTS OF NATASHA ROMANOFF IN BLACK WIDOW: A SEARLEAN ANALYSIS - Oki Ayu Saputri; Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2024)
Semantics is the study of meaning in language, including how the meanings of words and expressions relate to each other in various forms of discourse. One key branch of semantics is speech act theory, which examines how utterances function as actions. According to Austin, there are three types of speech acts: locutionary, illocutionary, and perlocutionary. This study focuses on illocutionary acts, which are intended actions performed by the speaker through speech. This research employs a descriptive qualitative method and analyzes the utterances of Natasha Romanoff in the movie Black Widow. The study aims to identify the types and purposes of illocutionary acts used by the main character. Based on Searle’s (1979) classification, illocutionary acts are divided into five types: (1) assertive, (2) directive, (3) commissive, (4) expressive, and (5) declarative. The results show that four types of illocutionary acts are found in Black Widow. In the assertive category, there are six data points used for stating, claiming, and predicting. In the directive category, there is one data point used for ordering. In the commissive category, four data points are found, used for threatening and refraining someone from doing something. Finally, in the expressive category, there are two data points used for condoling and complimenting. These findings reveal how language is used performatively in film to convey emotion, intent, and psychological depth.